Sistem Kendali dan Monitoring Cairan Infus pada Proses Tatalaksana Dehidrasi Berbasis IoT - Marta Diana; Kemalasari Kemalasari; Eru Puspita; Aji Sasongko Jati (Jurnal Rekayasa Elektrika, 2021)
Diarrhea is an endemic disease with Potential Extraordinary Events (PEE), often accompanied by death in Indonesia. Globally, at least diarrheal disease has caused 525,000 deaths in children each year, with the most severe threat being dehydration. It takes a system that can determine the degree of dehydration and manage dehydration quickly and appropriately to reduce the mortality rate. This study created a system to assess the degree of dehydration and perform the dehydration management process automatically. The method of determining the degree of dehydration using heart rate parameters and the process of justification is measured physical condition. In the process of dehydration management, intravenous fluid administration is carried out automatically using servo motors. To improve safety in infusion users, infusion volume, flow obstruction, air bubble, and rising blood detection are also carried out. All results will be processed on the microcontroller and will be sent to the ESP32 via serial communication. The data processing results will be connected using the Internet of Things so medical personnel can monitor via the website. The results showed that the average error of heart rate measurement using the moving average method of 0.41%, and the accuracy value in the infusion control system reached 90%.